Country familiarity in the initial stage of foreign market selection - Clark, Daniel R; Li, Dan; Shepherd, Dean A (Journal of International Business Studies, 2018)
Focusing on the initial stage of foreign market selection (i.e., narrowing a set of potential countries from which to make a final choice), we theorize that manager’s country familiarity influences both the decision-making process and outcome. We hypothesize that with increasing country familiarity, (a) manager investment of cognitive effort (process) first increases and then decreases, and (b) the likelihood of a country being included for further consideration (outcome) also increases and then decreases. We further hypothesize that the effects of country familiarity are contingent on the managers’ international experience. Empirical evidence from verbal protocol analyses of managers provides strong support to our arguments. These findings contribute to the emergent literature on the critical role of cognition in decision making about foreign markets. Manager cognition potentially influences sequential/non-sequential entry decision making, possibly explaining some previously observed exceptions to internationalization process theory. The contingent role of international experience further stresses that the influence of cognition in internationalization decision making is both important and complex, involving, at least, innate cognitive processes, idiosyncratic knowledge, and international experience. We discuss the theoretical implications, along with practice implications, of country familiarity and intuitive decision making in foreign market selection.